Respuesta :
a^2 + b^2 = c^2...where a and b r the legs and c is the hypotenuse
35^2 + b^2 = 37^2
1225 + b^2 = 1369
b^2 = 1369 - 1225
b^2 = 144...by taking the sqrt of both sides, this eliminates the ^2 on left
b = sqrt 144
b = 12...so ur other leg is 12 <==
35^2 + b^2 = 37^2
1225 + b^2 = 1369
b^2 = 1369 - 1225
b^2 = 144...by taking the sqrt of both sides, this eliminates the ^2 on left
b = sqrt 144
b = 12...so ur other leg is 12 <==
use Pythagorean theorem
a^2 + b^2 = c^2
Since 37 is the hypotenuse it will go in for 'c'.
a^2 + 35^2 = 37^2
a^2 + 1225 = 1369
Subtract 1225 from both sides.
a^2 = 144
Take the square root of both sides.
a = 12
The missing length is 12
a^2 + b^2 = c^2
Since 37 is the hypotenuse it will go in for 'c'.
a^2 + 35^2 = 37^2
a^2 + 1225 = 1369
Subtract 1225 from both sides.
a^2 = 144
Take the square root of both sides.
a = 12
The missing length is 12